Positive electrode material and preparation method thereof, battery and electric device
By preparing LiMn2-x1-x2M1x1M2x2O4 cathode material and combining it with a three-stage sintering process, the problem of insufficient grain boundary stability and safety of lithium manganese oxide cathode material at high temperatures was solved, achieving a balance between high capacity, low cost and fast charging performance, which is suitable for batteries and power devices.
Patent Information
- Application Number
- CN202511218595.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-11-28
AI Technical Summary
Existing lithium manganese oxide cathode materials have shortcomings in balancing high capacity, low cost, fast charging performance, and good cycle performance, especially in terms of safety and grain boundary stability at high temperatures, which need to be improved.
Using LiMn2-x1-x2M1x1M2x2O4 compound as the cathode material, a near-single-crystal structure cathode material was prepared by controlling the aggregation degree of secondary particles and the proportion of small-angle grain boundaries, combined with a three-stage sintering process. This improved the material's structural compactness and lithium-ion diffusion path, and reduced electrolyte side reactions.
It achieves a balance between high capacity, low cost, excellent fast charging performance and good cycle performance, and improves the high temperature stability and safety of the material, making it suitable for large-scale production.
Smart Images

Figure CN121035199A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular to a positive electrode material, a preparation method thereof, a battery and an electric device. BACKGROUND
[0002] The positive electrode material is a key component of a battery, which determines the energy density and cycle life of the entire battery. Spinel lithium manganate LiMn2O4 is one of the common positive electrode materials of lithium ion batteries, which has the advantages of low production cost, high working voltage, simple synthesis process, good thermal stability, superior rate performance and low temperature performance. Polycrystalline lithium manganate material has high initial capacity, low cost and good fast charging performance, but has poor high-temperature cycle and safety performance; while single-crystal lithium manganate material has less side reaction with electrolyte, good cycle performance of the material, and is not prone to crystal boundary fracture or phase change at high temperature, and has better safety performance, but has poor fast charging performance and capacity. How to obtain a positive electrode material with high capacity, low cost, good fast charging performance, good cycle performance and good safety performance is one of the challenges currently faced. SUMMARY
[0003] The present application aims to at least partially solve one of the technical problems in the related art. To this end, the present application provides a positive electrode material with high capacity, low cost, good fast charging performance, good cycle performance and good safety performance, and a preparation method thereof, a battery and an electric device.
[0004] In a first aspect, the present application provides a positive electrode material. According to an embodiment of the present application, the positive electrode material comprises a compound shown in Formula 1:
[0005] LiMn 2-x1-x2 M1 x1 M2 x2 O4 Formula 1
[0006] In Formula 1, 0.001≤x1≤0.1, 0≤x2≤0.2, M1 elements include at least one of B, Nb and W, and M2 elements include at least one of Al, Ni, Co, Mg, Zn, Cr, Cu, Ti and Y;
[0007] The positive electrode material comprises secondary particles, the secondary particles comprise a plurality of primary particles, and satisfy:
[0008] The aggregation degree is greater than or equal to 90%;
[0009]
[0010] The aggregation degree represents the percentage of the number of secondary particles comprising 4-40 primary particles in the total number of positive electrode material particles; D50 represents the average equivalent circle diameter of the grains of the positive electrode material obtained by EBSD test statistics.
[0011] The positive electrode material has a quasi-single crystal structure, and has the characteristics of high initial capacity, low cost, and good fast charging performance of polycrystalline positive electrode material, and less side reaction between single crystal positive electrode material and electrolyte, good cycle performance of material, less grain boundary fracture or phase change at high temperature, and better safety, which can balance performance and cost, and has better comprehensive use performance. Specifically, the aggregation degree is greater than or equal to 90%, which indicates that the structure of the positive electrode material is compact, which is beneficial to improving the volume energy density, and the agglomeration of the primary particles shortens the lithium ion diffusion path, which is beneficial to improving the fast charging performance and capacity performance. Further, Satisfying the above conditions can balance the capacity and cycle life, and further the positive electrode material has excellent comprehensive performance.
[0012] According to the embodiments of the present application, the small-angle grain boundary ratio δ of the positive electrode material satisfies: 7.0%≤δ≤11.5%.
[0013] According to the embodiments of the present application, the theoretical specific surface area BET1 of the positive electrode material and the real specific surface area BET2 of the positive electrode material satisfy:
[0014] 0.2≤BET2 / BET1≤0.6;
[0015] Wherein,
[0016] ρ is the real density of the positive electrode material.
[0017] According to the embodiments of the present application, the real specific surface area BET2 of the positive electrode material is 0.45m 2 / g to 0.70m 2 / g.
[0018] According to the embodiments of the present application, the D 50 of the positive electrode material is 4 microns to 15 microns.
[0019] In the second aspect of the present application, a method for preparing the positive electrode material described above is provided. According to the embodiments of the present application, the method comprises: mixing a manganese source, a lithium source, a first additive containing M1 elements, and a second additive containing M2 elements to obtain a mixture; and sequentially performing one-stage sintering, two-stage sintering, and three-stage sintering on the mixture to obtain the positive electrode material, wherein the temperature T2 of the two-stage sintering is not lower than the temperature T1 of the one-stage sintering, and the temperature T3 of the three-stage sintering is lower than the temperature T2 of the two-stage sintering; wherein the M1 elements include at least one of B, Nb, and W, and the M2 elements include at least one of Al, Ni, Co, Mg, Zn, Cr, Cu, Ti, and Y.
[0020] In the method, the first additive is added to have good fluxing effect, the single crystal-like morphology can be obtained in a suitable sintering temperature range, a large number of small crystal nucleus aggregates with a preliminary spinel structure can be obtained in the heating process, the grain growth can be controlled to the target size in the holding process, and then the interface reconstruction is performed through the annealing process of three-stage sintering to eliminate internal stress and repair material oxygen defects, so that the preparation process of low-temperature solid phase-crystal surface reconstruction is realized, the process is simple and controllable, the production cost is low, large-scale production can be realized, and the obtained positive electrode material has good comprehensive performance.
[0021] According to the embodiment of the present application, the molar ratio of manganese elements in the manganese source and lithium elements in the lithium source is 2:1.04-1.20.
[0022] According to the embodiment of the present application, the amount of the first additive is 0.01wt%-1wt% of the total mass of the manganese source and the lithium source.
[0023] According to the embodiment of the present application, the amount of the second additive is 0.05wt%-2wt% of the total mass of the manganese source and the lithium source.
[0024] According to the embodiment of the present application, the temperature T1 of the first-stage sintering is 450-550 DEG C.
[0025] According to the embodiment of the present application, the heating rate v1 of the first-stage sintering is 2-4 DEG C / min.
[0026] According to the embodiment of the present application, the holding time t1 of the first-stage sintering is 2-4 h.
[0027] According to the embodiment of the present application, the temperature T2 of the second-stage sintering is 800-900 DEG C, preferably 830-870 DEG C.
[0028] According to the embodiment of the present application, the heating rate v2 of the second-stage sintering is 2-4 DEG C / min.
[0029] According to the embodiment of the present application, the holding time t2 of the second-stage sintering is 6-12 h.
[0030] According to the embodiment of the present application, the temperature T3 of the third-stage sintering is 500-700 DEG C.
[0031] According to the embodiment of the present application, the cooling rate v3 of the third-stage sintering is 1-4 DEG C / min.
[0032] According to the embodiment of the present application, the holding time t3 of the third-stage sintering is 2-4 h.
[0033] According to an embodiment of the present application, the manganese source includes at least one of trimanganese tetroxide, manganese dioxide, manganese hydroxide, manganese carbonate, and manganese phosphate.
[0034] According to an embodiment of the present application, the manganese source has a D50 of 3.0 μm to 8.0 μm. 50
[0035] According to an embodiment of the present application, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium chloride.
[0036] According to an embodiment of the present application, the first additive includes at least one of niobium oxide, boride, and tungsten oxide.
[0037] According to an embodiment of the present application, the second additive includes at least one of nickel oxide, cobalt oxide, aluminum oxide, zinc oxide, chromium oxide, and fluoride.
[0038] In a third aspect, the present application provides a battery. According to an embodiment of the present application, the battery includes the cathode material described above or the cathode material prepared by the method described above. The battery has a good balance among capacity, rate performance, and cycle performance.
[0039] In a fourth aspect, the present application provides an electric device including the cathode material described above, the cathode material prepared by the method described above, or the battery described above. The electric device has all the features and advantages of the battery described above, which will not be repeated here. BRIEF DESCRIPTION OF DRAWINGS
[0040] Figure 1 EBSD test data of the single-crystal-like lithium manganate cathode material obtained in Example 1 of the present application.
[0041] Figure 2 SEM photo of the single-crystal-like lithium manganate cathode material obtained in Example 1 of the present application.
[0042] Figure 3 SEM photo of the single-crystal-like lithium manganate cathode material obtained in Comparative Example 1 of the present application.
[0043] Figure 4 SEM photo of the single-crystal-like lithium manganate cathode material obtained in Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0044] The embodiments described below are exemplary and are intended to explain the present application, but are not to be understood as limiting the present application.
[0045] The present application is based on the discovery and realization of the inventors on the following facts and problems:
[0046] As described above, the polycrystalline lithium manganate material has high initial capacity, low cost and good fast charging performance, but poor high-temperature cycle and safety; and the single-crystal lithium manganate material has less side reaction with electrolyte, good material cycle performance, less grain boundary fracture or phase change at high temperature, and better safety, but poor fast charging performance and capacity. The inventors have found that the quasi-single crystal, as a material for transition from polycrystal to single crystal, can have the common characteristics of polycrystal and single crystal, and by controlling the grain size, a quasi-single crystal morphology positive electrode material with submicron size can be obtained, which can have the characteristics of high capacity, low cost, good fast charging performance, good cycle performance and good safety.
[0047] Therefore, in a first aspect, the application provides a positive electrode material. According to an embodiment of the application, the positive electrode material comprises a compound shown in Formula 1:
[0048] LiMn 2-x1-x2 M1 x1 M2 x2 O4 Formula 1
[0049] In Formula 1, 0.001≤x1≤0.1, 0<x2≤0.2, M1 element comprises at least one of Nb, B and W, and M2 element comprises at least one of Al, Ni, Co, Mg, Zn, Cr, Cu, Ti and Y;
[0050] The positive electrode material comprises secondary particles, the secondary particles comprise a plurality of primary particles, and satisfy:
[0051] The aggregation degree is ≥90%;
[0052]
[0053] The aggregation degree represents the percentage of the number of secondary particles formed by 4-40 primary particles in the total number of positive electrode material particles; D50 represents the average equivalent circle diameter of the grains of the positive electrode material obtained by EBSD test statistics.
[0054] The positive electrode material has a quasi-single crystal structure, and has the characteristics of high initial capacity, low cost and good fast charging performance of polycrystalline positive electrode material, and less side reaction with electrolyte, good material cycle performance, less grain boundary fracture or phase change at high temperature, and better safety of single-crystal positive electrode material, which can balance performance and cost and have better comprehensive use performance. Specifically, the aggregation degree is ≥90%, which indicates that the structure of the positive electrode material is compact, which is beneficial to improving the volume energy density, and the agglomeration of the primary particles shortens the lithium ion diffusion path, which is beneficial to improving the fast charging performance and capacity performance, and the number of primary particles contained in the secondary particles is concentrated in 4-40, the positive electrode material has less grain boundary and defects, which is beneficial to improving the cycle life. Further, Satisfying the above conditions, the capacity and cycle life can be considered at the same time, and the positive electrode material has excellent comprehensive performance.
[0055] In this paper, the aggregation degree represents the percentage of secondary particles formed by 4-40 primary particles in the total positive electrode material particles. Specifically, the percentage of secondary particles formed by 4-40 primary particles in the total positive electrode material particles can be calculated by SEM photos of the positive electrode material (2K magnification, the total number of single particles and secondary particles is greater than 200).
[0056] In some embodiments, the aggregation degree is greater than or equal to 90%, specifically 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or any range between any two of them. Thus, the capacity, fast charging performance and cycle life of the positive electrode material can be better considered.
[0057] In this paper, EBSD test statistics of the average equivalent circle diameter of the grain of the positive electrode material. Specifically, the EBSD detector can be mounted on the SEM, the electron beam is irradiated on the inclined sample, the backscattered electrons are diffracted, the diffracted electrons are collected by software, the grain and interface microstructure characteristics of the collection area are obtained, and the average equivalent circle diameter of the grain is calculated.
[0058] In some embodiments, Specifically, It can be 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or any range between any two of them. Satisfying the above range, the primary particles can be closely packed, and the capacity can be high, while the contact area with the electrolyte is small, the side reaction is less, and the cycle performance is good.
[0059] According to the embodiments of the present application, the small angle grain boundary ratio δ of the positive electrode material satisfies: 7.0%≤δ≤11.5%, δ can be 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5% or any range between any two of them. Satisfying the above range, the small angle grain boundary can be used as the channel for the rapid diffusion of lithium ions, and the rate performance can be improved; if the small angle grain boundary is too much, it may hinder the diffusion of lithium ions across the grain boundary, and increase the impedance, if the small angle grain boundary is too less, the rate performance is limited.
[0060] In the present disclosure, the adjacent grain orientation angle difference (the minimum angle required to completely coincide the orientation of one grain with another grain after rotation) in the range of 2°-15° is defined as a small-angle grain boundary, which is mainly manifested as the dislocation structure of the grain. Specifically, the positive electrode material can be subjected to electron backscatter diffraction (EBSD) or transmission electron microscopy (TEM) orientation imaging, and the percentage of the length (or number) of the grain boundary satisfying the adjacent grain orientation angle difference in the range of 2°-15° in the total length (or number) of the grain boundary is calculated.
[0061] According to embodiments of the present application, the theoretical specific surface area BET1 of the positive electrode material and the real specific surface area BET2 of the positive electrode material satisfy: 0.2≤BET2 / BET1≤0.6 (specifically 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6 or any range between any two of them); wherein BET1=6 / (p x a); p is the real density of the positive electrode material. If the above range is satisfied, the positive electrode material can exhibit higher capacity, while having less side reaction with the electrolyte and better cycle performance. If the value of BET2 / BET1 is too large, the positive electrode material may have more side reactions with the electrolyte and more serious Mn dissolution, thereby having poorer cycle performance; if the value of BET2 / BET1 is too small, the positive electrode material may have poorer wettability with the electrolyte, thereby possibly leading to poor initial capacity and rate performance.
[0062] In the present disclosure, the real specific surface area BET2 of the positive electrode material can be tested by a specific surface instrument of Tristar3020 model of Micromeritics Company, and the real density of the positive electrode material can be tested by an AccuPyc II TEC model of a temperature-controlled gas displacement method density instrument of Micromeritics Company.
[0063] According to embodiments of the present application, the real specific surface area BET2 of the positive electrode material is 0.45m 2 / g to 0.70m 2 / g, specifically 0.45m 2 / g, 0.48m 2 / g, 0.50m 2 / g, 0.52m 2 / g, 0.55m 2 / g, 0.58m 2 / g, 0.60m 2 / g, 0.62m 2 / g, 0.65m 2 / g, 0.68m 2 / g, 0.70m 2 / g or any two of the above ranges. Meeting these ranges indicates that the cathode material has a suitable degree of fragmentation, with relatively light particle adhesion, allowing for more complete particle dissociation, good wettability with the electrolyte, and a low content of fine powder, which is beneficial for capacity utilization and reduces side reactions.
[0064] According to embodiments of this application, the D of the positive electrode material 50 The range is 4 micrometers to 15 micrometers, specifically 4 micrometers, 5 micrometers, 6 micrometers, 7 micrometers, 8 micrometers, 9 micrometers, 10 micrometers, 11 micrometers, 12 micrometers, 13 micrometers, 14 micrometers, 15 micrometers, or any two of these ranges. Meeting these ranges results in a cathode material with high compaction density, a shorter lithium-ion transport path, which is beneficial for improving rate performance. Furthermore, it reduces side reactions between the cathode material and the electrolyte, leading to better cycle performance.
[0065] In a second aspect, this application provides a method for preparing the aforementioned cathode material. According to an embodiment of this application, the method includes: mixing a manganese source, a lithium source, a first additive containing element M1, and a second additive containing element M2 to obtain a mixture; sequentially subjecting the mixture to a first-stage sintering, a second-stage sintering, and a third-stage sintering to obtain the cathode material, wherein the second-stage sintering temperature T2 is not lower than the first-stage sintering temperature T1, and the third-stage sintering temperature T3 is lower than the second-stage sintering temperature T2; wherein element M1 includes at least one of B, Nb, and W, and element M2 includes at least one of Al, Ni, Co, Mg, Zn, Cr, Cu, Ti, and Y.
[0066] In this method, the addition of a first additive has a good fluxing effect, which can obtain a near-single crystal morphology in a suitable sintering temperature range. The heating process can obtain a large number of small crystal nuclei with preliminary spinel structures. The holding process can control the growth of grains to the target size. Then, the interface reconstruction is carried out through a three-stage sintering annealing process to eliminate internal stress and repair oxygen defects in the material, thereby realizing the preparation process of low-temperature solid-phase-crystal plane reconstruction. The process is simple and controllable, has low production cost, can achieve large-scale production, and the obtained cathode material has good comprehensive performance.
[0067] According to embodiments of this application, the manganese source includes at least one of manganese tetroxide, manganese dioxide, manganese hydroxide, manganese carbonate, and manganese phosphate. Therefore, the material is widely available and has a low cost.
[0068] According to an embodiment of this application, the manganese source D 50 The particle size ranges from 3.0 μm to 8.0 μm, specifically within the ranges of 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or any two of these ranges. Within this range, it is advantageous to obtain cathode materials with the target particle size.
[0069] According to the embodiment of the present application, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium chloride. In this way, the material source is wide and the cost is low.
[0070] According to the embodiment of the present application, the molar ratio of manganese element in the manganese source and lithium element in the lithium source is 2:1.04-1.20, specifically, 1:1.04, 1:1.06, 1:1.08, 1:1.10, 1:1.12, 1:1.14, 1:1.16, 1:1.18, 1:1.20, or a range between any two of them. Within the above ratio range, the manganese source and the lithium source can fully react to obtain the lithium manganate positive electrode material.
[0071] According to the embodiment of the present application, the first additive includes at least one of niobium oxide, boride, and tungsten oxide. In this way, the fluxing effect can be better, which is beneficial to obtain the positive electrode material meeting the requirements.
[0072] According to the embodiment of the present application, the amount of the first additive is 0.01wt%-1wt% of the total mass of the manganese source and the lithium source, specifically, 0.01wt%, 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, or a range between any two of them. Within the above amount range, the fluxing effect can be better, and the positive electrode material with the target size can be obtained. If the content is too much, the size of the positive electrode material can be too large, and if the content is too little, the fluxing effect can not be obvious, and the effect of improving the performance of the positive electrode material is insufficient.
[0073] According to the embodiment of the present application, the second additive includes at least one of nickel oxide, cobalt oxide, aluminum oxide, zinc oxide, chromium oxide, and fluoride. In this way, the structural stability of the positive electrode material can be further improved, and the comprehensive performance of the positive electrode material can be further improved.
[0074] According to the embodiment of the present application, the amount of the second additive is 0.05wt%-2wt% of the total mass of the manganese source and the lithium source, specifically, 0.05wt%, 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2.0wt%, or a range between any two of them. Within the above amount range, the structural stability of the positive electrode material can be better improved, and the cycle performance of the positive electrode material can be further improved.
[0075] According to the embodiments of the present application, the temperature T1 of the first sintering is 450-550℃, specifically 450℃, 480℃, 500℃, 520℃, 550℃ or a range between any two of them. In the temperature range, the manganese source can be fully lithiated, and a large number of fine primary spinel structure crystal nucleus aggregates can be obtained.
[0076] According to the embodiments of the present application, the temperature T1 of the first sintering is 450-550℃, specifically 450℃, 480℃, 500℃, 520℃, 550℃ or a range between any two of them. In the temperature range, the manganese source can be fully lithiated, and a large number of fine primary spinel structure crystal nucleus aggregates can be obtained.
[0077] According to the embodiments of the present application, the temperature T1 of the first sintering is 450-550℃, specifically 450℃, 480℃, 500℃, 520℃, 550℃ or a range between any two of them. In the temperature range, the manganese source can be fully lithiated, and a large number of fine primary spinel structure crystal nucleus aggregates can be obtained.
[0078] According to the embodiments of the present application, the temperature T1 of the first sintering is 450-550℃, specifically 450℃, 480℃, 500℃, 520℃, 550℃ or a range between any two of them. In the temperature range, the manganese source can be fully lithiated, and a large number of fine primary spinel structure crystal nucleus aggregates can be obtained.
[0079] According to embodiments of the present application, the temperature T2 of the second sintering is 800-900℃, and specifically can be 830-870℃. For example, the temperature T2 of the second sintering can be 800℃, 810℃, 820℃, 830℃, 840℃, 850℃, 860℃, 870℃, 880℃, 890℃, 900℃, or a range between any two of them. Within the above temperature range, the atoms can be provided with higher energy, the atomic migration ability is stronger, and the atoms can be arranged with higher order, so that the positive electrode material with better crystal quality and fewer defects is obtained, and the structure stability of the positive electrode material is further improved, and the comprehensive performance of the positive electrode material is further improved.
[0080] According to embodiments of the present application, the holding time t2 of the second sintering is 6-12h, and specifically can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, or a range between any two of them. Within the above range, the crystal grains can be grown to a suitable size, and the positive electrode material meeting the target requirements is obtained; if the time is too short, the crystal grains cannot be fully grown, and if the time is too long, the crystal grain size can be too large, and the positive electrode material with the best comprehensive performance cannot be obtained.
[0081] According to embodiments of the present application, the cooling rate v3 of the third sintering is 1-4℃ / min, and specifically can be 1℃ / min, 1.2℃ / min, 1.5℃ / min, 1.8℃ / min, 2℃ / min, 2.2℃ / min, 2.4℃ / min, 2.6℃ / min, 2.8℃ / min, 3.0℃ / min, 3.2℃ / min, 3.4℃ / min, 3.6℃ / min, 3.8℃ / min, 4.0℃ / min, or a range between any two of them. Within the above range, the raw materials can be uniformly heated, and the formation of the crystal nucleus aggregate is further promoted, and the positive electrode material meeting the target requirements is obtained.
[0082] According to embodiments of the present application, the temperature T3 of the third sintering is 500-700℃, and specifically can be 500℃, 520℃, 550℃, 580℃, 600℃, 620℃, 650℃, 680℃, 700℃, or a range between any two of them. Within the above temperature range, the internal stress can be effectively eliminated, and the defects can be repaired, and the positive electrode material with higher crystal quality is obtained.
[0083] According to embodiments of the present application, the holding time t3 of the three-stage sintering is 2h-4h, specifically, 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4.0h or any range between any two of them. Within the above time range, the stress in the sintered product can be fully released, and the defects can be effectively recovered, thereby obtaining a high-multiplying low-dislocation positive electrode material.
[0084] In a third aspect, the present application provides a battery. According to embodiments of the present application, the battery comprises the positive electrode material described above or the positive electrode material prepared by the method described above. The battery takes into account the capacity, rate performance and cycle performance.
[0085] It can be understood that the specific type of the battery is not particularly limited, and can be a primary battery or a secondary battery. The shape of the battery can be a cylindrical battery, a square battery or any other shaped battery, etc. According to the outer packaging classification, the battery can be a hard-shell battery, a soft-pack battery, etc.
[0086] Generally, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding or stacking process. The electrode assembly and the electrolyte can be contained in an outer packaging. During the charging and discharging process of the battery, lithium ions are inserted and extracted between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the short circuit of the positive and negative electrodes, and at the same time to allow the lithium ions to pass through.
[0087] In some embodiments, the positive electrode sheet can comprise a positive electrode current collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode current collector. The positive electrode active material layer comprises the positive electrode material described above, a conductive agent and a binder. The positive electrode current collector can comprise a metal foil, for example, the metal foil can be an aluminum foil. The conductive agent can comprise acetylene black, single-walled carbon nanotubes and conventional materials in the art. The binder can be polyvinylidene fluoride (PVDF) and conventional materials in the art.
[0088] In some embodiments, the negative electrode sheet can include a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, the negative electrode active material layer can include a negative electrode active material, a thickening agent, a conductive agent, and a binder, wherein the negative electrode current collector can be a metal foil, for example, the metal foil can be a copper foil. The negative electrode active material can include artificial graphite, natural graphite, silicon-containing carbon-based composite material, lithium metal-containing composite material, lithium metal material, and conventional negative electrode active materials in the art. The thickening agent can be a thickening agent sodium carboxymethyl cellulose (CMC-Na) and conventional materials in the art. The conductive agent can be acetylene black and conventional materials in the art. The binder can be butadiene rubber and conventional materials in the art.
[0089] In some embodiments, the separator can be a separator commonly known in the art that can be used for lithium ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, and the like.
[0090] The fourth aspect of the present application provides a power consuming device comprising the positive electrode material as described above, the positive electrode material prepared by the method as described above, or the battery as described above. The power consuming device has all the features and advantages of the battery as described above, which will not be repeated here.
[0091] In some embodiments, the power consuming device can include a mobile device (such as a mobile phone, a notebook computer, and the like), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, and the like), an electric train, a ship and a satellite, an energy storage system, and the like, but is not limited thereto.
[0092] Embodiments of the present application are described in detail below.
[0093] Embodiment 1
[0094] (1) According to the molar ratio of manganese element to lithium element of 2:1.08, 1.0%wt (calculated based on the total mass of manganese source and lithium source, the same hereinafter) Al2O3, 0.5%wt Nb2O5, 0.1%wt Y2O3 are added, lithium carbonate, trimanganese tetraoxide, aluminum oxide, niobium oxide and yttrium oxide are mixed in a high-speed mixer, the obtained mixture is placed in a square sagger, cut into pieces and placed in a muffle furnace, and oxygen atmosphere is introduced.
[0095] (2) One-stage sintering: holding temperature is 500℃, heating rate is 2℃ / min, and holding time is 2h; two-stage sintering: holding temperature is 850℃, heating rate is 2℃ / min, and holding time is 8h; three-stage sintering: holding temperature is 600℃, cooling rate is 2℃ / min, and holding time is 2h; cooling, crushing and sieving to obtain a single-crystal-like lithium manganate (LiMn2O4).1.95 Al 0.04 Nb 0.008 Y 0.002 O4).
[0096] Example 2
[0097] The same as Example 1, the main difference being that 1%wt Nb2O5was added.
[0098] Example 3
[0099] The same as Example 1, the main difference being that 0.25%wt Nb2O5was added.
[0100] Example 4
[0101] The same as Example 1, the main difference being that an additional 0.10%wt H3BO3was added.
[0102] Example 5
[0103] The same as Example 1, the main difference being that 0.1% Y2O3was replaced by 0.25%wt MgO.
[0104] Example 6
[0105] The same as Example 1, the main difference being that the temperature of the second sintering stage was 815°C.
[0106] Example 7
[0107] The same as Example 1, the main difference being that the temperature of the second sintering stage was 895°C.
[0108] Example 8
[0109] The same as Example 1, the main difference being that the temperature of the second sintering stage was 4h.
[0110] Example 9
[0111] The same as Example 1, the main difference being that the temperature of the second sintering stage was 12h.
[0112] Example 10
[0113] The same as Example 1, the main difference being that 0.25%wt Nb2O5was added and the temperature of the second sintering stage was 825°C,
[0114] Example 11
[0115] The same as Example 1, the main difference being that an additional 0.25%wt WO3was added and the temperature of the second sintering stage was 875°C,
[0116] Example 12
[0117] The same as example 1, the main difference is that 1.2%wt Al2O3 is added, and the soaking temperature of the second sintering is 875℃,
[0118] Comparative Example 1
[0119] The same as example 1, the main difference is that the soaking temperature of the second sintering is 750℃.
[0120] Comparative Example 2
[0121] The same as example 1, the main difference is that the soaking temperature of the second sintering is 950℃.
[0122] Comparative Example 3
[0123] The same as example 1, the main difference is that no Nb2O5 is added.
[0124] Comparative Example 4
[0125] The same as example 1, the main difference is that 0.1%wt Nb2O5 is added, and the soaking temperature of the second sintering is 775℃.
[0126] Comparative Example 5
[0127] The same as example 1, the main difference is that 0.5%wt H3BO3 is additionally added.
[0128] Performance test:
[0129] (1) Morphology test: The SEM photos of the positive electrode materials in example 1, comparative example 1 and comparative example 2 are shown in Figure 2 , Figure 3 and Figure 4 respectively, which are obtained by Regulus 8100 model scanning electron microscope of Japan Hitachi company. It can be seen from Figures 2-4 that the surface of the single crystal-like particles has the characteristics of single crystal particle surface round and smooth, and is tightly connected by multiple primary particles.
[0130] (2) Aggregation degree: The percentage of the number of secondary particles with 4-40 primary particles in the SEM photos of the positive electrode materials in the total positive electrode material particles is counted.
[0131] (3) Particle size D 10 , D 50 , D 90 : Obtained by laser particle size instrument of Mastersizer 3000 model of Marvern company.
[0132] (4) Specific surface area (BET2) test: tested by a specific surface area tester of Tristar 3020 model of Micromeritics Company.
[0133] (5) EBSD test: the positive electrode material was cut by CP using Thermo Scientific CleanMill, then was pasted on an inclined stage at 70°, and was placed in a vacuum chamber. An EBSD detector was mounted on a SEM, and a standard mode ETD probe was selected for shooting. An electron beam was irradiated on the inclined sample, and backscattered electrons were diffracted to collect EBSD data. The collected EBSD data were opened using AZtec crystal software, and data noise was removed by clicking sample clean up. The data were screened by selecting equivalent circle diameter in the Grain Size interface, and were plotted to obtain the primary grain distribution data of the test area. The grain boundary data were determined according to the orientation difference of the primary grains, and the threshold values of large-angle grain boundaries and low-angle grain boundaries were set to 15° and 2° respectively by selecting the Grain boundaries option when plotting, so that the proportion of low-angle grain boundaries in the test area was obtained. The EBSD test data of the positive electrode material in Example 1 are shown in Table 1. Figure 1 Figure 1 It can be seen from the EBSD test data that the lithium manganate positive electrode material obtained in Example 1 has a single crystal-like morphology, that is, a large particle is composed of multiple primary particles, the average particle size of the primary particles is 1.14 μm, and the proportion of low-angle grain boundaries is 8.09%, and the dislocations are less.
[0134] (6) True density test: tested by an AccuPyc II TEC model temperature-controlled gas displacement method densimeter of Micromeritics Company.
[0135] (7) Battery performance detection:
[0136] 1) Battery preparation:
[0137] LiMn 1.95 Al 0.04 Nb 0.008 B 0.002 O4 positive electrode active material, conductive carbon black and polyvinylidene fluoride (PVDF) were mixed uniformly at a mass ratio of 95:3:2 with an appropriate amount of N-methyl pyrrolidone (NMP), and the slurry was coated on an aluminum foil and placed in a vacuum drying box at 120°C for 12 h. After drying, the slurry was punched into a positive electrode sheet with a diameter of 11 mm and a thickness of 3.2 mm using a pressure of 100 MPa, wherein the area density of the positive electrode sheet was 133.5 g / m 2 The negative electrode sheet uses a metal lithium sheet with a diameter of 11 mm and a thickness of 1 mm. The separator uses a polypropylene microporous film (Celgard 2325) with a thickness of 25 μm. The electrolyte uses an equal mixture of 1 mol / L LiPF6, ethylene carbonate (EC) and diethyl carbonate (DEC). The assembly is performed in an argon atmosphere glove box with a water and oxygen content <5 ppm. After the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte are assembled into a CR2025 button cell, the button cell is left to stand for 6 h.
[0138] 2) Battery test
[0139] In the examples and comparative examples, the CR2025 button cell is subjected to electrochemical performance testing using a Shenzhen Xinwei battery test system. The voltage window of the button cell is 3.0 V-4.3 V, the nominal specific capacity is 110 mAh / g, and the 0.1 C capacity is tested at 25°C;
[0140] High temperature test: 45°C, voltage range 3.0 V-4.3 V, 0.1 C charge and discharge for one cycle, 1 C cycle for 80 cycles, and the capacity retention rate is calculated to evaluate the high temperature cycle performance;
[0141] Low temperature impedance test:
[0142] -20°C low temperature capacity retention rate test: the button cell is activated at 25°C for 1 C charge and discharge for 1 week, 1 C charge and discharge for the second week, and the capacity is recorded as B1. After the third week, the button cell is transferred to a -20°C constant temperature box for 3 h, and then discharged at 1 C. The capacity is recorded as B2. The -20°C low temperature capacity retention rate is B2 / B1 x 100%.
[0143] -20°C 10% SOC-DCR1 test: after the button cell is activated at 25°C for 1 C charge and discharge for 1 week, the button cell is transferred to a -20°C constant temperature box for 2 h after 1 C charging to 10% SOC, and then discharged at 1 C for 20 s. The -20°C 10% SOC-DCR is (the voltage of the last second of the standby step - the voltage of the 20 s discharge) / discharge current.
[0144] -20°C 20% SOC-DCR2 test: after the button cell is activated at 25°C for 1 C charge and discharge for 1 week, the button cell is transferred to a -20°C constant temperature box for 2 h after 1 C charging to 20% SOC, and then discharged at 1 C for 20 s. The -20°C 120% SOC-DCR is (the voltage of the last second of the standby step - the voltage of the 20 s discharge) / discharge current.
[0145] Low temperature discharge test:
[0146] After 0.1C activation for one circle (4.3V cut-off) at room temperature 25℃, 0.5C charge to 30% SOC. Then transfer to -20℃ low temperature cabinet, rest for 1.5h, 0.5C discharge to 3.0V, the time used is the low temperature discharge duration.
[0147] Table 1: Physico-chemical indexes of positive electrode materials
[0148]
[0149] Table 2: Battery performance
[0150]
[0151]
[0152] From Table 2, the quasi-single-crystal lithium manganate has high capacity of polycrystalline lithium manganate and long cycle of single-crystal lithium manganate, and the performance of low-temperature retention rate, low-temperature impedance and low-temperature discharge duration of the quasi-single-crystal lithium manganate is also very excellent. The elements Nb, W and B have a certain fluxing effect in lithium manganate, and a certain amount of Nb, W and B element doping can not only obtain quasi-single-crystal lithium manganate with suitable morphology, but also improve the electrical performance of the material.
[0153] In the description of the present application, it should be understood that the terms "first", "second" are only for the purpose of description, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first", "second" can be explicitly or implicitly included at least one of the features. In the description of the present application, the meaning of "a plurality of" is at least two, such as two, three, etc., unless otherwise specifically limited.
[0154] In the description of the present application, the description of the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In the present application, the illustrative description of the above terms is not necessarily for the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any suitable manner in any one or more embodiments or examples. In addition, the skilled in the art can combine and combine the different embodiments or examples described in the present application and the features of the different embodiments or examples without contradiction.
[0155] Although the embodiments of the present application have been shown and described above, it should be understood that the above embodiments are exemplary and cannot be understood as limiting the present application, and those skilled in the art can make changes, modifications, replacements and variations to the above embodiments within the scope of the present application.
Claims
1. A positive electrode material, characterized in that, Including the compounds shown in Formula 1: LiMn 2-x1-x2 M1 x1 M2 x2 O4 type 1 In Formula 1, 0.001≤x1≤0.1, 0<x2≤0.2, element M1 includes at least one of Nb, B and W, and element M2 includes at least one of Al, Ni, Co, Mg, Zn, Cr, Cu, Ti and Y; The positive electrode material includes secondary particles, which in turn include multiple primary particles, and satisfies the following conditions: Aggregation degree ≥90%; Among them, the aggregation degree represents the percentage of secondary particles formed by 4 to 40 primary particles in the total number of cathode material particles; This represents the average equivalent circle diameter of the grains of the cathode material obtained from EBSD testing statistics.
2. The cathode material according to claim 1, characterized in that, The small-angle grain boundary ratio δ of the cathode material satisfies: 7.0% ≤ δ ≤ 11.5%.
3. The cathode material according to claim 1, characterized in that, The theoretical specific surface area BET1 of the cathode material and the actual specific surface area BET2 of the cathode material satisfy the following: 0.2≤BET2 / BET1≤0.6; Wherein, BET1 = 6 / (ρ×ā); ρ is the actual density of the cathode material.
4. The cathode material according to claim 1, characterized in that, The actual specific surface area (BET2) of the cathode material is 0.45 m². 2 / g~0.70m 2 / g.
5. The positive electrode material according to claim 1, characterized in that, The positive electrode material D 50 The size ranges from 4 micrometers to 15 micrometers.
6. A method for preparing the cathode material according to any one of claims 1 to 5, characterized in that, include: The manganese source, lithium source, first additive containing element M1, and second additive containing element M2 are mixed to obtain a mixture. The mixture is subjected to first-stage sintering, second-stage sintering and third-stage sintering in sequence to obtain the positive electrode material. The temperature T2 of the second-stage sintering is not lower than the temperature T1 of the first-stage sintering, and the temperature T3 of the third-stage sintering is lower than the temperature T2 of the second-stage sintering. The M1 element includes at least one of B, Nb, and W, and the M2 element includes at least one of Al, Ni, Co, Mg, Zn, Cr, Cu, Ti, and Y.
7. The method according to claim 6, characterized in that, At least one of the following conditions must be met: The molar ratio of manganese in the manganese source to lithium in the lithium source is 2:1.04 to 1.20; The amount of the first additive is 0.01 wt% to 1 wt% of the total mass of the manganese source and the lithium source; The amount of the second additive is 0.05 wt% to 2 wt% of the total mass of the manganese source and the lithium source.
8. The method according to claim 6, characterized in that, At least one of the following conditions must be met: The sintering temperature T1 of the first section is 450℃~550℃; The heating rate v1 of the sintering section is 2℃ / min to 4℃ / min; The holding time t1 for the first sintering stage is 2h to 4h; The temperature T2 of the two-stage sintering is 800℃~900℃, preferably 830℃~870℃; The heating rate v2 of the two-stage sintering is 2℃ / min to 4℃ / min; The holding time t2 for the two-stage sintering is 6h to 12h; The sintering temperature T3 for the three stages is 500℃~700℃. The cooling rate v3 of the three-stage sintering is 1℃ / min to 4℃ / min; The holding time t3 for the three-stage sintering is 2h to 4h.
9. The method according to claim 6, characterized in that, At least one of the following conditions must be met: The manganese source includes at least one of manganese tetroxide, manganese dioxide, manganese hydroxide, manganese carbonate, and manganese phosphate; The manganese source D 50 Its thickness ranges from 3.0 μm to 8.0 μm; The lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium chloride; The first additive includes at least one of niobium oxide, boron compounds, and tungsten oxide; The second additive includes at least one of nickel oxide, cobalt oxide, aluminum oxide, zinc oxide, chromium oxide, and fluoride.
10. A battery, characterized in that, The cathode material includes any one of claims 1 to 5 or the cathode material prepared by any one of claims 6 to 9.
11. An electrical appliance, characterized in that, The cathode material includes any one of claims 1 to 5, the cathode material prepared by any one of claims 6 to 9, or the battery as described in claim 10.
Citation Information
Patent Citations
Spherical or quasi-spherical lithium ion battery positive electrode material and lithium ion battery
CN107359334A
Lithium nickel manganate positive electrode active material, and preparation method for same and secondary battery using same
WO2023230832A1
Spinel-type lithium manganate, preparation method thereof, lithium-ion battery, and electrical apparatus
WO2024222955A1